Diabetic Retinal and Choroidal Edema in SDT Rats. (13th December 2015) - Toyoda, Fumihiko; Tanaka, Yoshiaki; Shimmura, Machiko; Kinoshita, Nozomi; Takano, Hiroko; Kakehashi, Akihiro
Abstract : We evaluated the features of diabetic retinal and choroidal edema in Spontaneously Diabetic Torii (SDT) rats. We measured the retinal and choroidal thicknesses in normal Sprague-Dawley (SD) rats( n = 9 ) and SDT rats( n = 8 ) . The eyes were enucleated 40 weeks later after they were diagnosed with diabetes, and 4-micron sections were cut for conventional histopathologic studies. The mean retinal and choroidal thicknesses were significantly thicker in the SDT rats than in the normal SD rats. The choroidal thickness was correlated strongly with the retinal thickness in both rat models. Diabetic retinopathy (DR) and diabetic choroidopathy appeared as edema in the SDT rats. The retinal thickness was correlated strongly with the choroidal thickness in the SDT rats, which is an ideal animal model of both DR and choroidopathy.